Single-Cell Photothermal Analysis Induced by MoS2 Nanoparticles by Raman Spectroscopy - Rusciano, Giulia; Capaccio, Angela; Sasso, Antonio; Singh, Manjot; Valadan, Mohammadhassan; Dell’Aversana, Carmela; Altucci, Lucia; Altucci, Carlo (Frontiers in Bioengineering and Biotechnology, 2022)
Two-dimensional nanomaterials, such as MoS2 nanosheets, have been attracting increasing attention in cancer diagnosis and treatment, thanks to their peculiar physical and chemical properties. Although the mechanisms which regulate the interaction between these nanomaterials and cells are not yet completely understood, many studies have proved their efficient use in the photothermal treatment of cancer, and the response to MoS2 nanosheets at the single-cell level is less investigated. Clearly, this information can help in shedding light on the subtle cellular mechanisms ruling the interaction of this 2D material with cells and, eventually, to its cytotoxicity. In this study, we use confocal micro-Raman spectroscopy to reconstruct the thermal map of single cells targeted with MoS2 under continuous laser irradiation. The experiment is performed by analyzing the water O-H stretching band around 3,400 cm−1 whose tetrahedral structure is sensitive to the molecular environment and temperature. Compared to fluorescence-based approaches, this Raman-based strategy for temperature measurement does not suffer fluorophore instability, which can be significant under continuous laser irradiation. We demonstrate that irradiation of human breast cancer MCF7 cells targeted with MoS2 nanosheets causes a relevant photothermal effect, which is particularly high in the presence of MoS2 nanosheet aggregates. Laser-induced heating is strongly localized near such particles which, in turn, tend to accumulate near the cytoplasmic membrane. Globally, our experimental outcomes are expected to be important for tuning the nanosheet fabrication process.